Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 2118 species occurrences available in GBIF matching the query: { "and" : [ "Country is Colombia", "HasGeospatialIssue is false", "Geometry POLYGON((-74.53 5.05,-74.53 5.33,-74.10 5.33,-74.10 5.05,-74.53 5.05))" ] } The dataset includes 2118 records from 50 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006107-160803222355964/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences